The aspirations and challenges of ethnic Malays' education towards egalitarian education in multiracial society - Idrus, Faizah; Ismail, Nik Ahmad Hisham (International Institute of Social and Economic Sciences & International Society for Academic Studies, z. s., 2019)
The purpose of this study is to examine teachers’ attitudes of towards egalitarian of education in multiracial society. This study used a quantitative method, using a survey. The survey is distributed to 500 Malay teachers, who are teaching in government school in peninsular of Malaysia. Malay teachers’ attitude towards egalitarian in education are measured statistically by four loading factors which are Malay Privileges, Environmental Support of Malay Privileges, Meritocracy and Standardized School System. The findings indicate that Malay teachers have a differing attitude towards Alternative Education for the Malays.